2017
DOI: 10.1002/cssc.201601494
|View full text |Cite
|
Sign up to set email alerts
|

Carbonate Ions Induce Highly Efficient Electrocatalytic Water Oxidation by Cobalt Oxyhydroxide Nanoparticles

Abstract: Synthetic models of oxygen evolving complex (OEC) are used not only to gain better understanding of the mechanism and the roles of cofactors for water oxidation in photosynthesis, but also as water oxidation catalysts to realize artificial photosynthesis, which is anticipated as a promising solar fuel production system. However, although much attention has been paid to the composition and structure of active sites for development of heterogeneous OEC models, the cofactors, which are essential for water oxidati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(41 citation statements)
references
References 52 publications
4
37
0
Order By: Relevance
“…has attracted much attention due to the leading catalytic performance and facile preparation ,. Recently, oxyhydroxide species such as amorphous CoO(OH), FeO(OH), NiO(OH) and CoFeO(OH) have been also proven as efficient catalysts for water oxidation ,,. In fact, Co−Pi and related catalysts are composed of small fragments/layers of CoO(OH) being responsible for water oxidation catalysis ,.…”
Section: Introductionsupporting
confidence: 77%
See 2 more Smart Citations
“…has attracted much attention due to the leading catalytic performance and facile preparation ,. Recently, oxyhydroxide species such as amorphous CoO(OH), FeO(OH), NiO(OH) and CoFeO(OH) have been also proven as efficient catalysts for water oxidation ,,. In fact, Co−Pi and related catalysts are composed of small fragments/layers of CoO(OH) being responsible for water oxidation catalysis ,.…”
Section: Introductionsupporting
confidence: 77%
“…The other band (relatively weak) at 532.5 eV is attributed to the oxygen from the adsorbed hydroxyl contamination on the film surface. These XPS spectra in Co 2p and O 1s regions for the CoO(OH)‐NS film those were nearly the same as those for CoO(OH)‐NP film, (Figure S1a and b), ensuring that the chemical state of CoO(OH) is close between the CoO(OH)‐NS and CoO(OH)‐NP films.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of bicarbonate or carbonate ions in the four‐electron oxidation of water to evolve O 2 has been frequently studied over various oxygen‐evolving catalysts such as Ni complex, Ru‐sensitizer/IrO 2 (colloidal system), CuSO 4 / Na 2 CO 3 system, Cu complex, and CoO(OH)/indium‐doped tin oxide (ITO) electrode . The carbonate cofactor was found to have multiple roles in the water oxidation cycle, such as buffer anion, proton acceptor, non‐innocent anion binding with central metal ion, and so on, in enhancing the catalytic activity of water oxidation catalysts.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, a high proton-transport capacity of the electrolyte is needed to prevent the formation of a local pH gradient. The choice of the electrolyte can strongly affect the catalytic performances [13] and has been the object of numerous literature studies [14][15][16][17][18][19]. In the Co oxide catalyst of the cobalt-phosphate type described first by Kanan and Nocera [20], we reported that the catalytic activity at high current density is proportional to the availability of unprotonated buffer molecules for a variety of tested buffer electrolytes [15].…”
Section: Introductionmentioning
confidence: 85%